Reimagining Curriculum Management For Future Ready Education A Systematic Review Of Emerging Strategies And Global Trends - Asep Kusmawan (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study systematically examines emerging strategies and global trends in curriculum management to understand how education systems can better prepare learners for the demands of the twenty-first century. Rapid technological advancements, increased global interconnectedness, and changing labour markets require a shift from traditional content-based curricula toward more adaptive, competency-oriented, and inclusive models. Using a systematic literature review approach, this study analysed 85 peer-reviewed articles published between 2010 and 2024, drawing from major academic databases including Scopus, Web of Science, ERIC, and ScienceDirect. The review followed PRISMA protocols for identification, screening, eligibility assessment, and synthesis, and applied thematic analysis to classify the literature into four major domains shaping contemporary curriculum reform. The findings reveal that curriculum management is increasingly driven by four interdependent pillars: leadership-driven curriculum governance, digital transformation, competency-based curriculum design, and inclusive planning supported by robust evaluation frameworks. Visionary and evidence-based leadership plays a critical role in enabling curriculum coherence and fostering collaborative professional cultures. Digital transformation expands learning opportunities and enhances instructional relevance but also exposes disparities in institutional readiness. Competency-based models support deeper learning and transferable skills, while inclusive curriculum approaches promote equity and responsiveness to student diversity. Collectively, these themes demonstrate that future-ready curriculum management requires systemic, adaptive, and equity-focused strategies that reflect global educational shifts. The study offers insights for policymakers, school leaders, and researchers seeking to advance resilient, innovative, and future-oriented curriculum reforms.